A potent small-molecule inhibitor of the DCN1-UBC12 interaction that selectively blocks cullin 3 neddylation - Haibin Zhou (Nature Portfolio, 2017)
Cullins are central components of the ubiquitin-proteosome system and are activated via a neddylation process mediated by the DCN1–UBC12 complex. Here, the authors develop a small molecule inhibitor of the DCN1–UBC12 interaction that specifically blocks cullin 3 neddylation and can be used to probe the cellular function of cullin 3.